Coordination of multiple non-holonomic agents with input constraints - Oikonomopoulos, Apollon S.; Loizou, Savvas; Kyriakopoulos, Kostas J. (My University, 2009)
In this paper we present a multi-agent coordination algorithm suitable for systems with aircraft-like kinematic constraints. A model of a system of input-constrained nonholonomic agents is constructed, suitable for use with formal verification tools. The agents considered are uniform and have bounded velocities and limited turning capabilities. We demonstrate how a model checker can be used to generate a counterexample trace for such a system, usable as a trajectory that satisfies our safety and liveness requirements. © 2009 IEEE.
Keywords: Formal verification tools; Input constraints; Kinematic constraints; Liveness; Model checker; Multi-agent coordinations; Nonholonomics